2010
DOI: 10.1080/15228861003754156
|View full text |Cite
|
Sign up to set email alerts
|

ICARDA'S Approach in Seed Delivery: Technical Performance and Sustainability of Village-Based Seed Enterprises in Afghanistan

Abstract: In the absence of organized formal public or private sector, finding an innovative alternative seed delivery remains a key challenge. ICARDA initiated a novel approach of establishing farmer-led village-based seed enterprises (VBSEs) to ensure rapid access to quality seed of adapted new crop varieties under the Alternative Livelihoods Program (ALP-E) on integrated staple crop development in eastern Afghanistan. This article describes VBSEs, their technical performance, profitability, and impact, and assesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Outcomes indicated that on overall basis, 34% respondents were involved in multiplication of their own seed. However, these findings can be coincided with Srinivas et al (2010) who reported that majority (53%) of farmers used/ multiplied their own produced seed; and 20% obtained seed from other farmers. 1, not at all information; 2, little information; 3, reasonable quantity of information; 4, more information; 5, much information.…”
Section: Farm Sizesupporting
confidence: 79%
“…Outcomes indicated that on overall basis, 34% respondents were involved in multiplication of their own seed. However, these findings can be coincided with Srinivas et al (2010) who reported that majority (53%) of farmers used/ multiplied their own produced seed; and 20% obtained seed from other farmers. 1, not at all information; 2, little information; 3, reasonable quantity of information; 4, more information; 5, much information.…”
Section: Farm Sizesupporting
confidence: 79%
“…In spite of concerted efforts from public and international research and development organizations, the dissemination and adoption of improved wheat varieties and associated good agricultural practices have not been improved as much as would have been expected. Regional studies show low seed/varietal replacement as one of the major reasons for low wheat yields in South Asia (Ortiz Ferrara et al, 2007; Rizvi et al, 2012; Srinivas et al, 2010; Thapa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The merit of the concept was tested on the farmers surveyed, and most responded favourably with 68% of respondents considering it could be a profitable and successful small-scale business. The idea did not originate from the farmers themselves but most were amenable to the idea of adoption and long-term commitment to this activity (Srinivas et al ., 2010). However, the participatory research approach could provide a sense of ownership to farmers and encourage them to make the idea their own thus ensuring better long-term success (Singh et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The notion of establishing VBFSEs in farming communities originated from Africa (David, 2004) as a sustainable approach to seed delivery. Many researchers evaluated this concept in their studies across Africa and Asia (Setimela et al ., 2004; Singh et al ., 2013; Srinivas et al ., 2010). It has been found to be very effective in developing a seed production and informal distribution systems in many situations.…”
Section: Discussionmentioning
confidence: 99%